Students' and teachers' perceptions of effective teaching and learning in the middle level science classroom: the effects on student achievement - NeSmith, Richard A. (Curtin University, 2003)
The major purpose of the study was to examine the relationship between teacherstudent interpersonal behaviour in the middle level of schooling with the students' academic achievement in science as determined by the term grade (typically issued after a six or nine week grading period). The study also provided validation data for the Questionnaire on Teacher Interactions (QTI) survey instrument with a large American sample of students and teachers drawn from randomly selected the State of Ohio schools. The QTI was designed to elicit students' and teachers' perspectives of effective teaching and learning in classrooms. Numerous studies, here and abroad, during the last five years and have caused awareness that students' perceptions of their school experience are a significant influence on how and what students learn in the classroom. Few studies have been conducted on the topic of student perceptions in comparison to their respective teachers' perceptions in science or how this variance might influence student achievement. The focus of the present study was to compare the perceptions of students and their teachers regarding effective teaching and learning, while concurrently noting students' achievement in science. This study presumed that there was a definite disparity between what teachers perceive to be effective teaching and learning in comparison to what students perceive. The intention of the study was to identify some of the factors associated with any disparity. The hypothesis for the study, simply stated, was that student achievement, according to student's accumulative grade, would reflect a variance in perception with that of their science teacher.Restated, the student's perception of effective teaching and learning could demonstrate to be a strong indicator of academic success or failure, depending upon the extent of difference with their respective teachers'. The research design of the study was based on the survey research method incorporating: 1) student and teacher questionnaires; 2) student and teacher interviews and; 3) students' science achievement, as measured in a teacher-issued grade. A probability sample of 433 middle school students was surveyed using the 48-item short form of the Australian version of the QTI (Wubbels, 1993). This sample comprised 21 middle level science classes, ranging from grade 5 through grade 9. Twelve cooperating science teachers associated with the teaching of science to these students were also surveyed using Questionnaire on Teacher Interaction (QTI). In addition, random interviews were conducted using interview logs with 6 teachers and 6 students selected from a convenience sample of those also responding to the questionnaire. Another major component of the research design was the term grade recorded by the cooperating science teacher, as a means of gauging "student academic achievement". All student and teacher questionnaire data were statistically analysed using Microsoft Excel 2000 and the Statistical Package for Social Science (SPSS) for Windows 1999. The analysis was according to the proper categories in the QTI based on leadership, helpful/friendly, understanding, student responsibility and freedom, uncertain, and dissatisfied, admonishing and strict behaviour established in the QTI.The use of both qualitative and quantitative data collection methods from a range of data sources provided a means of triangulation to strengthen the validity of the findings, which thus afforded a means of comparing data consistency and cross validation for the purpose of improving the rigour of the research design. As a means of collecting empirical data, schools were randomly chosen (probability sample) from the 20001-2002 Ohio Educational Directory, a directory produced by the Ohio Department of Education. Thirty-three schools were drawn. Between October 20002 and January 2003, each school was sent two letters inviting their participation in the study; one letter was sent to the on-site principal and one to the "head science teacher". Five weeks from the date the original letter was sent out to those not responding. Eventually, twenty-one classes returned their surveys for analysis. The Questionnaire of Teacher Interaction (QTI) was chosen due to its record of validity and its ease of administering. The qualitative data were tallied and recorded. The quantitative data analysis was completed using both manual and computerised methods to address the objectives of this study.